Oncogenic osteomalacia: loss of hypophosphatemia might be the key to avoid misdiagnosis - Chang, Cláudia; Conde, Sandro José [UNESP]; Luvizotto, Renata A. M. [UNESP]; Nunes, Vânia S. [UNESP]; Bonates, Milla C. [UNESP]; Felicio, Andre C.; Lindsey, Susan C. [UNESP]; Moraes, Flávia H. [UNESP]; Tagliarini, José V. [UNESP]; Mazeto, Glaucia M. F. [UNESP]; Kopp, Peter; Nogueira, Célia R. [UNESP] (My University, 2012)
Diagnosing oncogenic osteomalacia is still a challenge. The disorder is characterized by osteomalacia caused by renal phosphate wasting and low serum concentration of 1,25-dihydroxyvitamin D3 occurring in the presence of a tumor that produces high levels of fibroblast growth factor 23. However, it is possible that the disease is much more misdiagnosed than rare. We present the case of a 42-year-old man with a long-term history of undiagnosed progressive muscle weakness. His laboratory results mainly showed low serum phosphate. Surgical removal of a nasal hemangiopericytoma that had been diagnosed five years earlier, brought him to a symptom-free condition. Even though knowing the underlying etiology would explain his osteomalacia, the patient sought medical help from countless physicians for five consecutive years, and only after adequate treatment a rewarding outcome was achieved.

A osteomalacia oncogênica é um diagnóstico clínico desafiador, caracterizado pela perda renal de fosfato e baixos níveis de 1,25-di-hidroxivitamina D3 , ocorrendo na presença de um tumor produtor de altos níveis de fator de crescimento de fibroblasto 23. No entanto, é possível que se trate muito mais de uma falha de diagnóstico clínico do que propriamente uma doença rara. Os autores relatam o caso de um homem de 42 anos com histórico de fraqueza muscular progressiva por cinco anos e restrição à cadeira de rodas, sem diagnóstico. Seus exames laboratoriais evidenciavam baixos níveis de fósforo. A remoção cirúrgica de um hemangiopericitoma detectado previamente em cavidade nasal levou à resolução completa dos sintomas. Os autores enfatizam que, mesmo com a etiologia já evidenciada, o paciente consultou diversos clínicos no decorrer dos cinco anos até que fossem instituídos o diagnóstico e o tratamento adequados.
Osteomalacia oncogênica: a perda de fosfatemia pode ser a chave para evitar o diagnóstico incorreto